Introducing rapid diagnostic tests for malaria to drug shops in Uganda: a cluster-randomized controlled trial - Jessica Cohen; Günther Fink; Kathleen Maloney; Katrina Berg; Matthew Jordan; Theodore Svoronos; Flavia Aber; William Dickens
Objective To evaluate the impact - on diagnosis and treatment of malaria - of introducing rapid diagnostic tests to drug shops in eastern Uganda. Methods Overall, 2193 households in 79 study villages with at least one licensed drug shop were enrolled and monitored for 12 months. After 3 months of monitoring, drug shop vendors in 67 villages randomly selected for the intervention were offered training in the use of malaria rapid diagnostic tests and - if trained - offered access to such tests at a subsidized price. The remaining 12 study villages served as controls. A difference-in-differences regression model was used to estimate the impact of the intervention. Findings Vendors from 92 drug shops successfully completed training and 50 actively stocked and performed the rapid tests. Over 9 months, trained vendors did an average of 146 tests per shop. Households reported 22 697 episodes of febrile illness. The availability of rapid tests at local drug shops significantly increased the probability of any febrile illness being tested for malaria by 23.15% (P = 0.015) and being treated with an antimalarial drug by 8.84% (P = 0.056). The probability that artemisinin combination therapy was bought increased by a statistically insignificant 5.48% (P = 0.574). Conclusion In our study area, testing for malaria was increased by training drug shop vendors in the use of rapid tests and providing them access to such tests at a subsidized price. Additional interventions may be needed to achieve a higher coverage of testing and a higher rate of appropriate responses to test results.